Antiulcer Effect of Bark Extract of Tabebuia avellanedae: Activation of Cell Proliferation in Gastric Mucosa During the Healing Process. (12th September 2012) - Pereira, Isabela Tiemy; Burci, Lígia Moura; da Silva, Luisa Mota; Baggio, Cristiane Hatsuko; Heller, Melina; Micke, Gustavo Amadeu; Pizzolatti, Moacir Geraldo; Marques, Maria Consuelo Andrade; de Paula Werner, Maria Fernanda
Abstract : Tabebuia avellanedae (syn. Handroanthus impetiginosus ) is popularly known as 'ipê‐roxo' and has been used in folk medicine as anti‐inflammatory and in the treatment of ulcers, bacterial and fungal infections. This study evaluated the gastric ulcer healing property of the ethanolic extract (EET) of barks from Tabebuia avellanedae and investigated the mechanisms that may underlie this effect. Rats were treated with EET (twice a day for 7 days) after induction of chronic gastric ulcers by 80% acetic acid. Following treatment, histological and immunohistochemical analysis were performed in gastric ulcer tissues. Oral administration of EET (100 and 300 mg/kg) significantly reduced the gastric lesion induced by acetic acid in 44 and 36%, respectively. Histopathological evaluation demonstrated a contraction of gastric ulcer size, increase of mucus layer (periodic acid‐Schiff stained mucin‐like glycoproteins) and cell proliferation (proliferating cell nuclear antigen immunohistochemistry) in animals treated with EET (100 and 300 mg/kg). The results demonstrate that EET significantly accelerates healing of acetic acid induced gastric ulcer in rats through increase of mucus content and cell proliferation, indicating a potential usefulness for treatment of peptic ulcer diseases. Copyright © 2012 John Wiley & Sons, Ltd.